Geographical Distribution and Demographic Characteristics of Gestational Trophoblastic Disease - Soares, Patricia Daniela Paranhos B.; Maestá, Izildinha [UNESP]; Nunes Costa, Olivia Lucia; Charry, Rafael Cortes; Dias, Adriano [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Sci Printers & Publ Inc, 2010)
OBJECTIVE: To outline the geographical distribution pattern of gestational trophoblastic disease (GTD) in a referral center in Bahia, Brazil, and determine the demographics of the disease.STUDY DESIGN: We conducted a study of data retrieved from medical records of 140 GTD patients referred to our Trophoblastic Diseases Center in 2002-2007, assessing geographical distribution across health care districts, demographics, referral sources, and previous pregnancy status.RESULTS: The most common GTD types were hydatidiform mole (106, 75.7%), invasive mole (32, 22.9%), choriocarcinoma (1, 0.7%), and placental site trophoblastic tumor (1, 0.7%). GTD incidence was 8.5 in 1,000 deliveries. Most patients originated from the coastal region (East district), which includes the state capital (77.9%). The 20-34 age group predominated (65%). Education level (67.9% attended elementary school only) and employment rate (42.9%) were low. Secondary hospitals were the principal source of referral (84.3%), followed by self-referrals (15.7%). Regarding previous pregnancy status, 42.1% (n = 59) had had term pregnancy, 39.3% (n = 55) no pregnancy, 15% (n = 21) miscarriage, and 0.7% (n = 1) ectopic pregnancy; 4 patients (2.9%) had previous hydatidiform mole.CONCLUSION: GTD predominated in the peak fertility age group and among patients of unfavorable sociodemographic status. (J Reprod Med 2010;55:305-310)
Keywords: demographics; geographical distribution; gestational trophoblastic disease